Heat impact on schoolchildren in Cameroon, Africa: potential health threat from climate change - Tord Kjellstrom; Ekoe Tetanye; Georges Nguefack-Tsague; Léonie N. Dapi; Joacim Rocklöv (Taylor & Francis Group, 2010)
Background: Health impacts related to climate change are potentially an increasing problem in Cameroon, especially during hot seasons when there are no means for protective and adaptive actions. Objective: To describe environmental conditions in schools and to evaluate the impact of heat on schoolchildren's health during school days in the Cameroon cities of Yaoundé and Douala. Methods: Schoolchildren (N=285) aged 12–16 years from public secondary schools completed a questionnaire about their background, general symptoms, and hot feelings in a cross-sectional study. In Yaoundé, 50 schoolchildren were individually interviewed during school days about hourly symptoms (fatigue, headache, and feeling very hot) and performance. Lascar dataloggers were used to measure indoor classroom temperatures and humidity. Results: There was a significant correlation between daily indoor temperature and the percentages of schoolchildren who felt very hot, had fatigue, and headaches in Yaoundé. A high proportion of schoolchildren felt very hot (48%), had fatigue (76%), and headaches (38%) in Yaoundé. Prevalences (%) were higher among girls than boys for headaches (58 vs 39), feeling ‘very hot overall’ (37 vs 21), and ‘very hot in head’ (21 vs 18). Up to 62% were absentminded and 45% had slow writing speed. High indoor temperatures of 32.5°C in Yaoundé and 36.6°C in Douala were observed in school. Conclusions: Headache, fatigue, and feeling very hot associated with high indoor air temperature were observed among schoolchildren in the present study. Longitudinal data in schools are needed to confirm these results. School environmental conditions should be improved in order to enhance learning.